Legal Terminology and Lesser Used Languages: The Case of Mòcheno - Chiocchetti, Elena; Ralli, Natascia (Research in Language, 2011)
The article aims at outlining the specific problems connected with the elaboration of legal and administrative terminology in a lesser used language and illustrating the methods and tools proposed considering the knowledge and competences to be conveyed.Since 2003 the Institute for Specialised Communication and Multilingualism of the European Academy of Bolzano (EURAC) offers education courses in legal terminology work, coupled with introductions in related/complementary disciplines, e.g. documentation, specialised translation and technical writing. Next to professional trainings, the Institute held also ad-hoc courses, such as a two-day course organised in 2008 for the Mòcheni, a Germanic minority living in the Italian Province of Trento. Since the passing of provincial law no. 6/2008, which foresees specific measures for the protection and promotion of local language minorities, the Mòcheno-speaking community has the right to use their language in all situations of social, economic and administrative life in both oral and written communications. Notwithstanding the recent compilation of a standard grammar, the Mòcheno language is not yet developed for the use in technical and specialised contexts. Indeed, the most urgent needs seem to exist in the translation of administrative terminology.